WAYS OF REPRODUCING THE SEMANTICS OF VERBAL MEANS OF THE CONCEPT “NON/BREAD” IN THE TARGET LANGUAGE (International journal of artificial intelligence, 2025)
This article explores the challenges of reproducing the linguistic means of the “Non/Bread” concept in Uzbek and English translation. The study investigates literal and figurative meanings, their cultural semantic load, and the degree of equivalence in translation. Full, partial, and non-equivalences are analyzed across different linguistic levels with illustrative examples. Particular attention is given to phraseological units and proverbs containing the bread/non component, emphasizing their status as linguocultural markers. The research highlights the effectiveness of transliteration, descriptive translation, and mixed techniques in rendering culturally bound expressions. Findings demonstrate that cultural differences in conceptualizing bread require translators to rely on context, pragmatic meaning, and functional-stylistic features. The study concludes that adequate translation of bread-related units depends largely on the translator’s linguocultural competence and sensitivity to cultural nuances.